Pendampingan penyusunan Standar Operasional Prosedur pelayanan di Desa Petajen Kecamatan Bajubang Kabupaten Batang Hari - A Zarkasi; Riri Maria Fatriani (Unri Conference Series: Community Engagement, 2019)
The Procedures Standard Operating is a manifestation of a standard measure of providing quality services to the community and part of the basic tasks and functions of the state apparatus as public servants. In the process of providing services, it is required to have standard operating procedures for services in each implementing unit. Quality, fast, easy, affordable and measurable services can minimize deviations and decrease performance in service providers. This dedication activity has provided assistance to village government apparatus in compiling standard operating procedures by the dedication team of the Government Science Study Program, Faculty of Social and Political Sciences, Jambi University. The service method used is the lecture method, discussion using the prepared knowledge material and the practice of making standard service procedures directly accompanied by the dedication team. The location of community service activities was carried out in the Petajen Village, Bajubang District, Batang Hari Regency, Jambi Province. The results of the activity evaluation show that all village apparatus are very appreciative of the existence of mentoring activities in making standard operating procedures. This is expected to be able to maximize the service so that it can direct the community effectively, efficiently, consistently and full fill the standards.